2,6-Difunctionalization of N-Substituted Dithienothiazines via Dilithiation - Dostert, Catherine; Czajkowski, Daniel; Müller, Thomas J. J. (Synlett, 2014)
The regioselective lithiation of dithienothiazines followed by electrophilic trapping in a one-pot fashion is an efficient route to 2-mono- and 2,6-difunctionalized dithienothiazines. A pseudo five-component dilithiation–diformylation–double-Wittig olefination sequence gives a dithienothiazine symmetrically functionalized with α,β-unsaturated ester side chains in excellent yield.
Keywords: addition reactions; heterocycles; lithiation; multicomponent reactions; Wittig reactions